2015
DOI: 10.5812/ijem.22803
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Internet Therapeutic Intervention on Patients With Diabetes

Abstract: Background:With the emergence of IBGMS for allowing for patients to communicate their self-monitored blood glucose (SMBG) readings with their health care providers, their impact on the management of diabetes is becoming well-supported with regards to clinical benefits. Their impact on healthcare costs, however, has yet to be investigated. This study aims to determine the cost-benefits of such interventions in comparison to routine care.Objectives:To analyze the cost-benefit of an Internet Blood Glucose Monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Necessary adjustments to each patient's oral medications were communicated, and positive reinforcement was provided if no changes were needed. It is important to note that IBGMS reporting operated in parallel with the conventional standard of diabetes care; although IBGMS patients have been shown to visit their endocrinologists less frequently, 14 they were offered the same short-term and yearly follow-up appointments as non-IBGMS patients.…”
Section: Methodsmentioning
confidence: 99%
“…Necessary adjustments to each patient's oral medications were communicated, and positive reinforcement was provided if no changes were needed. It is important to note that IBGMS reporting operated in parallel with the conventional standard of diabetes care; although IBGMS patients have been shown to visit their endocrinologists less frequently, 14 they were offered the same short-term and yearly follow-up appointments as non-IBGMS patients.…”
Section: Methodsmentioning
confidence: 99%
“…This is in agreement with a retrospective Canadian study, evaluating cost-effectiveness, which showed a significant reduction in endocrinologist visits for diabetic patients in the telemedicine group compared with the control group. 20 Furthermore, a recent study published by Davidson also reported a pilot project using a remote glucose monitoring utilizing computerized insulin dose adjustment and results showed that the method was safe and effective while saving medical time and face-to-face visit. 21 However, it should be noted that our study reflected a short-term analysis for a 6-month period and that long-term impact on medical visits associated with THC monitoring remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…56 Furthermore, existing evidence suggest that with telemedical intervention higher costs reduction may occur due to less or shorter regular visits to the endocrinologist. 57 GM with CRI in combination with mobile apps are an optimal solution in digitalized health care systems, where smartphones are expected to be used by 70% to 90% of the world's population by 2020. 58 Differences in cost savings are likely due to heterogeneity in terms of costs of treatment of MI and hypoglycemic episodes.…”
Section: Discussionmentioning
confidence: 99%